O prêmio FINEP de inovação tecnológica - Rossino, Alexander Emoski Barbosa (2006)
The phenomenon of the innovation plays a central role in the analyses on the nature and the causes of the wealth of the nations and organizations, being a strategical and necessary factor for the development. In this direction, the Innovation in Brazil is promoted by the MCT (Ministry of Science and Technology), through the FINEP (Financier of Studies and Projects) that since 1998 it comes awarding innovative companies with Prize FINEP of Technological Innovation. The present work if considers to present a study of data handling of the Description of Editions of Prize FINEP of Technological Innovation since 1998 up to 2006, analyzing the procedures adopted in the Prize (commission judge, criteria of judgment, awarding, stages, categories), as well as the profile of the companies candidates and winners of the Prize, evaluating the current period of training of the same, collating the results gotten with the ones of the PINTEC (Industrial Research of Technological Innovation) of the IBGE (Brazilian Institute of Geography and Statistics). Being based on these premises, this work identified: the concept of innovation of the FINEP throughout the years, a standard of innovative companies in Brazil and its geographic distribution, as well as the importance of the Prize in the promotion of the Brazilian Innovation, according to lines of direction of the politics of Science, Technology & Innovation. Beyond these results, the established characterizations and comparisons essentially in carried through descriptive statisticians in this work will have to serve more of motivating material for the accomplishment of deepened studies on specific aspects that can contribute for the advance of the understanding of the promotion of technological innovation through prizes, in special, of those characteristic of developing countries. Key words: Prize Finep, technological innovation, technological development.